IMPROVING MOTIVATION AND LEARNING OUTCOMES OF AL-QUR'AN AND HADITH THROUGH THE STAD METHOD FOR SEVENTH GRADE STUDENTS OF MADRASAH TSANAWIYAH DARUL FATTAH - Yuli Fitriana; Muhammad Azamuddin Syahapala; Sahril Dwi Pamungkas; Rido Kurnianto; Sigit Dwi Laksana (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
The teaching of Al-Qur’an Hadith delivered by the 7th-grade Al-Qur’an Hadith teacher at MTs. Darul Fattah Galak Slahung Ponorogo uses a classical method. This is based on direct observations and interviews with the Al-Qur’an Hadith teacher, and it was also found that students' scores are still below the Minimum Completeness Criteria (KKM). Based on this issue, the researcher is interested in conducting research using the STAD method. The researcher aims to determine the increase in motivation and the extent of improvement in Al-Qur’an Hadith learning outcomes through the STAD method among 7th-grade students at Madrasah Tsanawiyah Darul Fattah. This study uses the Classroom Action Research (PTK) method conducted over 2 cycles, with each cycle consisting of 2 sessions. The instruments used are observations of student activities throughout the learning process from beginning to end, while test instruments are used to assess students' cognitive knowledge levels and learning outcomes. The results of activity observation as an assessment of motivation in learning in cycle I showed student activeness at 61.29%, and in cycle II it was 75.10%. There was an increase in the percentage of learning completeness from cycle I at 63.64% to cycle II at 91.18%, an increase of 27.54%. Thus, the STAD method can improve the motivation and learning outcomes of Al-Qur’an Hadith for seventh-grade students at Madrasah Tsanawiyah Darul Fattah.